Analisis Pemberitaan Patah Rangka eSAF Motor Honda pada CNN Indonesia - Muhamad Firzan Akbar; Bintang Awal Ramadhan ; Ahmad Fajar Mahendra; Muammar Khadafi; Tria patrianti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
This research was conducted to conduct an in-depth analysis of the interconnection between mass media coverage, corporate crises, and the role of media in shaping public perception, with a focus on the specific case of the eSAF Motor Honda's frame breakage reported by CNN Indonesia. The research employed a qualitative approach. The results of the study indicate that there was intensive coverage on CNN Indonesia, particularly in August, with an initially negative tone. Consumer responses influenced public perception and exerted pressure on the company. In other words, the reputation crisis faced by PT Astra Honda Motor requires effective and transparent communication management to address consumer concerns and restore the company's image. Companies need to maintain open and ongoing communication to support the recovery of their reputation.